2002
DOI: 10.1002/dc.10190
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid and myeloid neoplasms involving cerebrospinal fluid: Comparison of morphologic examination and immunophenotyping by flow cytometry

Abstract: We studied 53 samples of cerebrospinal fluid (CSF) by cytologic examination and immunophenotyping by flow cytometry. The samples were taken from 43 patients; 25 had a previous diagnosis of malignant lymphoma/leukemia and the remaining 18 a variety of other diseases involving the central nervous system (CNS). Lymphoma/leukemia was detected in 21 samples: 12 by morphologic examination and immunophenotyping and nine by immunophenotyping alone. There were two cases with a suspicious morphologic examination and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 20 publications
5
49
0
Order By: Relevance
“…15 Several reports have compared cytology with FC showing a broad range of concordant results. 4,9,10 Our FC findings and chimerism analysis in the group of patients relapsing in the CNS showed a high concordance degree. With the exception of three patients, agreement was observed between FC and chimerism analysis in 11 patients.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…15 Several reports have compared cytology with FC showing a broad range of concordant results. 4,9,10 Our FC findings and chimerism analysis in the group of patients relapsing in the CNS showed a high concordance degree. With the exception of three patients, agreement was observed between FC and chimerism analysis in 11 patients.…”
Section: Discussionsupporting
confidence: 61%
“…7,8 Furthermore, whereas several reports compare cytology with FC in the identification of CSF cells, there is no comparison between FC and chimerism analysis in this type of sample. 4,9,10 In this study, we evaluated the potential contribution of CSF donor-recipient chimerism analysis in patients with neurological symptoms following alloHCT. …”
mentioning
confidence: 99%
“…10,42,45,46 Early studies analyzing non-stabilized CSF samples by ≤4-color FCM already demonstrated increased sensitivity in between 3% and 20% of cases as compared with cytology (Table 2). 42,[47][48][49][50] More recent analyses of larger series of CSF-stabilized samples using 4-8 color FCM have confirmed the greater sensitivity of FCM vs. CC with a median proportion of occult CNSL (FCM+/CC-CSF) of 12% (range: 5%-13%) ( Table 1). 10,45,51 Patients with occult CNSL (i.e., CC-and FCM+ CSF) typically showed lower levels of CSF infiltration (<20% or <1 tumor B cell/μL) than FCM+/CC+ cases, 45 further supporting the greater sensitivity of FCM vs. CC.…”
Section: Multiparameter Flow Cytometry Analysis Of Csf Samplesmentioning
confidence: 88%
“…Although CSF analysis is essential for the management of intra-thecal treatment schedules, the diagnostic performance of either FCM or CM in the follow-up setting is mostly unknown [6,10,11]. Moreover, whether the two methods retain differential accuracy in different diagnostic subgroups is largely undetermined [2-4,6-9].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) analysis by flow cytometry (FCM) and cytomorphology (CM) is currently requested to explore central nervous system (CNS) involvement by hematologic malignancy, both at diagnosis and during follow-up [1][2][3][4][5][6][7][8][9][10][11]. To date, the two methods have been mostly studied on CSF from newly diagnosed cases, i.e., those optimally evaluable samples not liable to intrathecal treatment-related damage [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%